Treatment of hyperprolactinemia in women: A Position Statement from the Brazilian Federation of Gynecology and Obstetrics Associations (Febrasgo) and the Brazilian Society of Endocrinology and Metabolism (SBEM) - Benetti-Pinto, Cristina Laguna (2024)
Dopamine agonists are the first line of treatment for patients with symptomatic hyperprolactinemia due to prolactinomas and in those with idiopathic hyperprolactinemia. Treatment with these agents is effective in 80%-90% of the cases. Infertility treatment of patients with hyperprolactinemia is also carried out with dopamine agonists, aiming for the normalization of prolactin levels. The risk of symptomatic growth of prolactinomas during pregnancy is dependent on the tumor’s size, duration of previous treatments, and prolactin levels. Notably, the corresponding risk is relatively low in cases of microprolactinomas (<5%). Remission of hyperprolactinemia occurs in about 30% of the patients after drug treatment and may also occur after pregnancy and menopause. The use of some drugs, such as antidepressants and antipsychotics, is a frequent cause of hyperprolactinemia, and managing this occurrence involves unique considerations. This position statement by the Brazilian Federation of Gynecology and Obstetrics Associations (Febrasgo) and Brazilian Society of Endocrinology and Metabolism (SBEM) addresses the recommendations for measurement of serum prolactin levels and the investigations of symptomatic and asymptomatic hyperprolactinemia and drug-induced hyperprolactinemia in women.